Konstruksi Sosial Siswa Generasi Z dalam Memaknai Quater Life Crisis di Era Digital - Gita Febriana; Babul Bahrudin; Fika Anjana (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aims to explore the social construction of Quarter Life Crisis among Generation Z students in the digital era. Employing a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis. The research participants consisted of purposively selected twelfth-grade students, while supporting informants included guidance and counseling teachers, homeroom teachers, the school principal, and the students' parents or guardians. The collected data were analyzed using the Miles and Huberman interactive model of qualitative data analysis. The findings reveal that the social construction of the Quarter Life Crisis among Generation Z students at MA Darul Hasan is shaped through continuous interactions with family, school, peers, and social media. Most participants perceive the Quarter Life Crisis as a state of anxiety, confusion, and uncertainty regarding their future, particularly in relation to higher education, career aspirations, and life expectations.